Fertirrigação: técnicas e práticas de manejo - Gramasco, Giovanni Amadeu Parente (Universidade Federal de São Carlos, 2021)
Irrigation aims to expand the cultivation of various crops in non-occasional times, that is, at different times throughout the year, resulting in better results and yields from your crop. The use of the fertigation technique has had one of the greatest impacts in the agricultural sector, resulting in a greater and better distribution of nutrients throughout the entire crop cycle. The fertigation technique has been adopted by several producers, being used in different regions of the country due to the fact that it manages to increase the efficiency of nutrient absorption by that particular crop. One of the ways to obtain an increase in crop efficiency is the use of adequate water use in crops, being altered or leading to a possible increase in crop production. The types of irrigation are key points to carry out a more efficient and sustainable management, however, of all types of irrigation systems that currently exist, micro irrigation and drip systems are the ones that achieve the highest efficiency rates for water use. Another fact that everyone knows is that fertilization and crop nutrition are two essential factors, responsible for gains in productivity and in the quality of the final product; this is because the plant's nutritional balance is a fundamental condition for the maximum expression of its genetic potential. Thus, carry out evaluations of the characteristics of the fertilizers that will be used together with the irrigation water, since the fertilizer must be suitable for the type of irrigation, plant nutrition and the like. The fertigation technique adds several advantages, such as: fertilizers have their losses reduced by leaching and volatilization, and also their application efficiency is much higher when compared to the conventional way of application. Currently, in irrigation, it is clear how much the use of automation in irrigated systems has been growing. Thus, by definition automation are techniques which are based on electronic equipment whose function is to reduce labor and ensure quick solutions.
Fertigation: management techniques and practices
Keywords: Nutrição; Fertilizantes; Absorção; Solução do solo; Eficiência do uso da água; Irrigação; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA